Differences in respiratory arousal threshold in Caucasian and Chinese patients with obstructive sleep apnoea. Issue 5 (16th March 2017) - Lee, Richard W.W.; Sutherland, Kate; Sands, Scott A.; Edwards, Bradley A.; Chan, Tat on; S.S. NG, Susanna; Hui, David S.; Cistulli, Peter A.
ABSTRACT: Background and objective: Ethnic differences in obstructive sleep apnoea (OSA) phenotype may not be limited to obesity and craniofacial factors. The aims of the study were to (i) compare the proportion of Caucasians and Chinese patients with a low respiratory arousal threshold (ArTH) and (ii) explore the influence of anatomical compromise on ArTH. Methods: Interethnic comparison was conducted between cohorts of Caucasian and Chinese patients from specialist sleep disorder clinics. Polysomnography and craniofacial photography were performed. A low respiratory ArTH was determined by an ArTH score of 2 or above (one point for each: apnoea–hypopnoea index (AHI) < 30/h, nadir oxygen saturation (SaO2 ) > 82.5%, fractions of hypopnoeas > 58.3%). Anatomical compromise was stratified according to the photographic face width measurement. Results: A total of 348 subjects (163 Caucasians and 185 Chinese) were analysed. There was a significantly lower proportion of Chinese patients with moderate‐severe OSA (AHI ≥ 15) who had a low ArTH (28.4% vs 48.8%, P  = 0.004). This difference remained significant among those with severe OSA (AHI ≥ 30) (2.6% vs 17.1%, P  = 0.02). The proportion of moderate‐severe OSA Caucasians with a low ArTH was significantly less in those with severe anatomical compromise (36.6% vs 61.0%, P  = 0.03), whereas there was no difference in Chinese patients (25.5% vs 31.5%, P  = 0.49). Conclusion: Compared to Caucasians with severe OSA, a low respiratory ArTh appears to be a less common pathophysiological mechanism in Chinese patients. Caucasians with less severe anatomical compromise exhibit evidence of a lower ArTh, an association which is absent in Chinese patients. Our data suggest that OSA mechanisms may vary across racial groups. Abstract : Ethnic differences in obstructive sleep apnoea (OSA) pathophysiological mechanisms are unknown. This study shows that Chinese patients with moderate‐severe OSA are less likely to have a low respiratory arousal threshold compared with Caucasians. These findings highlight that ethnicity may need to be considered when tailoring therapies for OSA. See Editorial, page 847